2021
DOI: 10.3390/molecules26092594
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, and Inhibition of Acetylcholinesterase Potentials of Cassia timoriensis DC. Flowers

Abstract: Despite being widely used traditionally as a general tonic, especially in South East Asia, scientific research on Cassia timoriensis, remains scarce. In this study, the aim was to evaluate the in vitro activities for acetylcholinesterase (AChE) inhibitory potential, radical scavenging ability, and the anti-inflammatory properties of different extracts of C. timoriensis flowers using Ellman’s assay, a DPPH assay, and an albumin denaturation assay, respectively. With the exception of the acetylcholinesterase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 81 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…Our previous screening of 17 methanolic extracts from C. fistula, C. alata, C. spectabilis, C. timoriensis, and C. grandis showed that C. timoriensis and C. grandis exhibited promising AChE inhibitory activity [ 27 ]. Additionally, our group analyzed different extracts of C. timoriensis flowers for phytochemical analysis and inhibitory activity [ 28 ]. It was found that ethyl acetate, methanol, and hexane extract of C. timoriensis with IC 50 values of 6.91, 6.40, and 12.08 µg/mL, respectively, were a promising option for further chemical investigation [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous screening of 17 methanolic extracts from C. fistula, C. alata, C. spectabilis, C. timoriensis, and C. grandis showed that C. timoriensis and C. grandis exhibited promising AChE inhibitory activity [ 27 ]. Additionally, our group analyzed different extracts of C. timoriensis flowers for phytochemical analysis and inhibitory activity [ 28 ]. It was found that ethyl acetate, methanol, and hexane extract of C. timoriensis with IC 50 values of 6.91, 6.40, and 12.08 µg/mL, respectively, were a promising option for further chemical investigation [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, our group analyzed different extracts of C. timoriensis flowers for phytochemical analysis and inhibitory activity [ 28 ]. It was found that ethyl acetate, methanol, and hexane extract of C. timoriensis with IC 50 values of 6.91, 6.40, and 12.08 µg/mL, respectively, were a promising option for further chemical investigation [ 28 ]. Based on the previous AChE screening results along with TLC profiling, only n -hexane and ethyl acetate extracts were chosen for further chemical analysis and purification.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that this is the first study on the enzyme inhibitory activity of the four species against these enzymes except for C. grandis , where a previous study on the pulp of the fruit reported its α-glucosidase inhibition [ 37 ]. Alhawarri et al [ 38 ] reported that the high anti-AChE activity of Cassia timoriensis was positively correlated to its high phenolic and flavonoids. Phenolic compounds with anti-AChE activity were suggested to improve the signal transmission in nerve synapses and increase the concentration of ACh in synapses between cholinergic neurons [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…An example of what can happen with crude extracts from parts of plants is the recent article by Alhawarri et al 5 in the journal Molecules , (an open access journal). Page 3 of that article has a listing of the “assays” utilized, followed by a discussion of many of the classes of molecules that were “considered to be present.” However, many of the compounds listed were identified using what in basic analytical chemistry are known as spot tests.…”
Section: A Recent Example Of Problems Using Natural Product Extractsmentioning
confidence: 99%